Contingency factors influencing MAS design of manufacturing firms in Malaysia - Siow, Yung Ern; Amalina Abdullah; Foong, Soon Yau (Penerbit Universiti Kebangsaan Malaysia, 2016)
From a contingency framework, this paper empirically examines the relationship between decentralization, advanced manufacturing technology (AMT) and market competition on the adoption of sophisticated management accounting system (MAS) design among manufacturing firms in Malaysia. Using a structured questionnaire and regression analysis, data from 137 manufacturing firms from Malaysia show that the sophistication of MAS adopted is significantly and positively related with AMT adoption and market competition. The findings suggests that the adoption of sophisticated MAS design is parallel with the adoption of advanced manufacturing innovations and is able to assist firms to cope with the changes in the business environment. However, a positive but insignificant relationship was observed in the relationship between decentralization and MAS design. These results have contributed to the management accounting change literature by suggesting that attempts by the MAS designers to improve the timeliness and the scope of the information are of particular relevance to the managers of the firm.